CodeGeek: A Next-Generation Coding Platform with AI- Driven Feedback - Dr. Madhur Jain,; Dr. Shilpi Jain,; Nipun Baryah, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
As the demand for online coding platforms continues to rise, developers require efficient and feature-rich environments for coding practice and problem-solving. CodeGeek is a web-based coding platform designed to enhance programming education and competitive coding by offering real-time code execution, an AI- powered coding assistant, and a comprehensive problem repository. This platform is built on the MERN stack, leveraging MongoDB for data storage, Express.js for backend functionality, React.js for the user interface, and Node.js for server-side execution. To enhance the coding experience, it integrates Monaco Editor for interactive coding and supports multiple programming languages via the Judge0 API [1][2][12][13]. With CodeGeek, users can write, test, and optimize their code against predefined test cases, ensuring accuracy and efficiency. The AI-driven assistant provides contextual hints, debugging support, and performance insights, helping users improve their coding skills. Looking ahead, planned enhancements include coding contests, broader language support, and a diverse range of programming challenges to foster a dynamic learning environment. By integrating modern web technologies and AI-powered assistance, CodeGeek strives to create an engaging and intelligent coding platform tailored to students, developers, and competitive programmers, enhancing both learning and problem-solving efficiency.
Keywords: Online Coding Platform; MERN Stack; Judge0 API; Competitive Programming; AI Code Assistant; Code Execution